(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
Hydraulic segmental sluices of the water level entering reservoirs through rivers or canals Qp value and the required level of the reservoir Qd is an adjusting and controlling structure designed to control the difference between values.